Implementasi Algoritma Apriori Menggunakan Tanagra Pada Coffe Ayos Untuk Mengetahui Pola Penjualan - Rambe, Inny Rahayu; Juledi, Angga Putra; Nasution, Marnis (Universitas Labuhanbatu, 2024)
Caffe Ayos is a cafe that is quite famous in the Rantauprapat area, but that doesn't mean it doesn't have competition in business. With so many new cafes popping up, of course this could have quite a significant impact if Ayos cafe doesn't first create a strategy to stay afloat. Apart from improving service and maintaining the taste of the menu, there needs to be other things done by Café Ayos, and with the many transactions that occur every day, of course there is a pile of data. From this pile of data, it is hoped that it can provide new knowledge that will be useful later for Café Ayos. Knowledge can be extracted from daily sales transaction data using Acsociation Rule data mining. From the extraction results, we obtained several foods and foods that depend on each other, which have a confidence of up to 70% to 100%. It would be better to create special packages for several menus that are related to high confidence values, thereby providing more attraction.